Plastic-inhabiting fungi in marine environments and PCL degradation activity - Sung Hyun Kim; Jun Won Lee; Ji Seon Kim; Wonjun Lee; Myung Soo Park; Young Woon Lim (Antonie van Leeuwenhoek, 2022)
Plastic waste has a negative impact on marine ecosystems and the quantity of this source of anthropogenic pollution continues to increase. Several studies have investigated plastic biodegradation using various microorganisms. In this study, we isolated fungi from polyethylene terephthalate (PET) waste on Korean seacoasts and evaluated their ability to degrade plastic by comparing the diameters of the clear zones they formed on polycaprolactone (PCL) agar. We isolated 262 strains from 47 plastic waste sources and identified 108 fungal species via molecular methods. The PCL agar assay revealed that 87 species presented with varying degrees of PCL degradation capacity. Among them, certain fungal species were strong PCL degraders. The present study demonstrated the possibility that some fungi inhabiting plastic could potentially degrade it in the marine environment. We believe that the discoveries made herein lay theoretical and practical foundations for the development of novel bioremediation systems for marine plastispheres and help mitigate the environmental pollution issues related to plastic wastes.